Working Together. Multi Purpose Programs for Troubled Youth - Kuhn, Deborah; Pressman, Harvey; Benchmarks, Inc., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This paper provides program planners with some innovative ideas that have been used in all phases of various multi-service programs for high-risk youth. Chapter 2 focuses on strategies for assessing participant needs. Diagnosis, learning disabilities and remediation, and staff training are discussed. Chapter 3 considers elimination of service gaps through such support services as transportation, child care, medical examinations, emergency loans, housing, food stamps, legal aid, and family life and parenthood education. The next five chapters discuss approaches to these services offered by youth programs: job development and training, basic skill development, counseling, recreation and cultural enrichment, and youth involvement and self-advocacy. In chapter 9 ideas are included for developing links and connections with other community services, agencies, and resources to prevent fragmentation of service delivery to youth at risk. Chapter 10 describes some multiple funding possibilities, problems faced and overcome, and program results. A bibliography lists contacts and addresses of projects mentioned in the text, organizations and agencies that help connect programs with resources, and publications of practical value to practitioners. (YLB)
Sponsoring Agency: Edna McConnell Clark Foundation, New York, NY.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Ancillary School Services; Basic Skills; Career Development; Career Education; Community Cooperation; Community Support; Counseling Services; Cultural Enrichment; Disadvantaged Youth; Educational Diagnosis; Employment Programs; Federal Aid; Federal Programs; Financial Support; High Risk Students; Job Development; Job Placement; Job Training; Learning Disabilities; Linking Agents; Needs Assessment; Out of School Youth; Program Development; Recreation; Remedial Instruction; Secondary Education; Social Services; Student Participation; Youth Employment; Youth Programs; Guides, Non-Classroom.; Reports, Descriptive